IMPLEMENTASI WEBSITE SEBAGAI SISTEM INFORMASI MANAJEMEN PENDIDIKAN PADA SEKOLAH ISLAM TERPADU (SIT) AL-HIKMAH AMANAH UMMAH MAROS - Arifin, Nurqarirah; Damopolii, Muljono; Hasan, Mardhiah (MPI STAI Sangatta Kutai Timur, 2024)
This research aims to analyze the implementation of a Website as an Educational Management Information System at Al-Hikmah Amanah Ummah Integrated Islamic School in Maros. This research adopts a qualitative approach with the phenomenological method, which is a research approach that focuses on an in-depth understanding of individuals' subjective experiences related to the observed phenomenon. The data sources consist of primary data from in-depth interviews with the principal and system operators, direct observation of system use, and secondary data in related document analysis. The study results show that the Educational Management Information System at Al-Hikmah has significantly contributed to improving the efficiency and effectiveness of educational management. Analysis of the data obtained from interviews, observations, and document analysis indicates that access to information through the school's website enables stakeholders, such as students' parents, teachers, school staff, and the general public, to obtain accurate and up-to-date information about the school's vision and mission, flagship programs, activity documentation, school-related news, the student enrollment menu, as well as the addresses and contacts of the Integrated Islamic Kindergarten, Integrated Islamic Junior High School, Integrated Islamic Senior High School, and Al-Hikmah Amanah Ummah Tahfidz Boarding School units. This research is expected to contribute to the development of educational management information systems in similar institutions and provide insights into information technology's critical role in improving educational management quality.